The Effects of a Pandemic on Patient Engagement in a Patient-Reported Outcome Platform at Orthopaedic Sports Medicine Centers (106). Issue 10 (31st October 2021) - Barnds, Brandon; Witt, Atlee; Orahovats, Alexanda; Schlegel, Theodore; Hunt, Kenneth
Objectives: Patient-reported outcomes (PROs) are an important clinical tool to effectively collect, compile, and assess patient data and clinical progress. Beyond just tracking patient progress, PROs facilitate patient-provider communication and can be used to inform care practices. Though recent studies have focused on the merits of PRO collection in orthopaedics, few have sought to understand the impact of the coronavirus pandemic on PRO collection. Our objective is to review the initialization of an electronic PRO collection platform at our Orthopaedic Sports Medicine clinics and surgery center before and during the coronavirus pandemic. We focus specifically on our first 7, 557 patients in a retrospective study and the interplay between our collection tactics and the patients' responses to PROs from November 2019 to July 2020. Methods: Starting in the fall of 2019, we implemented a new clinic-wide data capturing system to collect PROs and maintain our outcomes database. We began with a small group of providers and their patients before expanding to include most providers and staff in three clinics. Patients received the following forms prior to their first visit: Patient-Reported Outcome Measurement Information System (PROMIS) Pain Interference, PROMIS Physical Function, and subsequent corresponding anatomic-specific scales. The Brief Resilience Scale (BRS) was later added in the spring of 2020. A secure link to the surveys was sent to the patient's email or phone prior to their appointment or accessed via an iPad at the clinic's kiosk during their appointment. However, due to coronavirus cleaning protocols, forms were only sent to the patient's email or phone beginning in March. Upon completion of July 2020 collection, we utilized STATA statistical software to analyze the data and identify trends in patient responses. For statistical analysis, we used chi-squared tests. Results: For the purpose of this study, we collected PROs from 7, 557 patients between November 2019 and July 2020. After analyzing all data points in STATA, we determined differences in several collection categories, including the extent of completion and time of completion. Out of all patients prompted to complete one or more PROs, 37.20% of patients (n = 2811) did not complete any PROs, 11.86% of patients (n = 896) completed some but not all assigned PROs, and 50.95% of patients (n = 3850) completed all assigned PROs. Patients who completed all or some of their PROs completed them before their appointment 56.02% of the time (n = 2773), within an hour of their appointment 35.49% of the time (n = 1757), and after their appointment 8.48% of the time (n = 420) (see Figure 1). After separating PRO completion rates by month, we noticed a shift in compliance and patient response patterns before and during the coronavirus pandemic. From November to February, the average number of patients who completed one or more PROs was 80.20% (n = 1797) before dropping to an average of 57.74% (n = 5760; p <0.001) between March and July. The overall PRO compliance rate similarly dropped at our first PRO collection site, Clinic A, from an average of 86.75% to 76.81%, respectively (see Figure 2). Clinic operations were significantly reduced in late March due to the coronavirus pandemic, leading to majority telehealth visits and restrictions on clinic-wide shared iPad use. Though more than half of patients on average completed their PROs prior to their appointment throughout the year, this trend was especially prevalent during the coronavirus pandemic. For all or some PROs completed prior to appointment time, 42.34% were completed on average between November and February compared to 62.42% between March and July (see Figure 3). Beyond completion metrics, we observed a difference in appointment cancellations before and during the coronavirus pandemic. From November to February, 21.28% of patient appointments were canceled on average compared to 35.74% of appointments canceled on average from March to July. The number of cancelations during the coronavirus pandemic was significantly different than before the pandemic (p <0.001). Conclusions: In a short period of time (9 months) after initial implementation of a PRO platform, our practice has amassed significant data and reported outcomes for over 7, 000 patients. Prior to the coronavirus pandemic, patients were relatively receptive to the new PRO collection platform with over 80% of patients completing some or all assigned PROs. However, following our clinic-wide cessation of shared iPads due to coronavirus concerns, we noted a significant decrease in our patient compliance (80.20% down to 57.74%; p <0.001). Though discontinuation of iPad and kiosk use likely only contributed in part to this significant decrease, this observation still suggests that shared devices may play an important role in promoting PRO compliance within the clinic. It's also important to note the limitations in this study, including the staggered integration of each provider's patients. This likely impacted the increased compliance rates in November with 282 patients versus 1677 patients in July. In addition, compliance may have been affected by the transition from two research staff members helping collect PROs to one research staff member. Methods of promoting compliance also changed as we shifted to telehealth visits. In March and April, members of our research team called patients about their incomplete PROs, likely prompting increased responses prior to patient appointments. We are utilizing these observations to improve our workflow for collecting patient PROs and increase compliance within the clinic. After reflecting on our initial findings, we feel the use of devices in clinic and full staff involvement can bolster completion of PROs and are important tools in order to best maintain a data collection platform with high patient compliance.